THE ROLE OF VISCOUS DISSIPATION IN THE OROGENIC PROCESS - Kincaid C.; Silver P. (My University, 1996)
The recognition that much of the mountain building within the continents can be attributed to the collision and deformation of tectonic plates has revolutionized geology over the last 25 years. Although the model of a deformed, advectively thickened plate accounts for the elevation of mountains and thick crustal roots usually associated with orogenies, it often has difficulty explaining the thermal properties of the mantle, namely the absence of a correspondingly thickened subcontinental lithosphere (SCL). Excess heat within the SCL associated with orogenies has been explained with models in which cool lithosphere is removed and replaced with warm asthenosphere. However, such lithosphere removal models are difficult to reconcile with recent seismic anisotropy studies suggesting the deformed SCL is not removed. We propose that evidence suggesting excess heat within, and long term survival of, SCL may be reconciled with anisotropy data sets by considering the heat generated by the orogeny itself. We develop a model of mantle orogeny where viscous strain-rate heating is considered as an energy source. Numerical experiments show that the SCL is rapidly heated during orogeny, resulting in elevated heat transfer between the lithosphere and overlying crust, but without necessarily removing the deformed SCL. Results also indicate that, for stress levels of > 200 MPa, viscous dissipation leads to spatial patterns of excess heat generation which are consistent with seismic profiles showing anomalously slow and fast material at shallow and deep levels, respectively. The ability of the viscous heating model to provide an in situ mantle heat source without removing patches of upper mantle provides an argument for lithospheric stresses in the 200 300 MPa range, which are in excess of those typically associated with orogenies.